Correction: A p-type multi-wall carbon nanotube/Te nanorod composite with enhanced thermoelectric performance. Issue 19 (20th March 2020) - Park, Dabin; Ju, Hyun; Oh, Taeseob; Kim, Jooheon
Abstract : Correction for 'A p-type multi-wall carbon nanotube/Te nanorod composite with enhanced thermoelectric performance' by Dabin Park et al., RSC Adv., 2018, 8, 8739–8746.